PRINT TO PLATFORM A VISUAL-DESIGN COMPARISON OF CREDIBILITY CUES IN INDIAN NEWSPAPERS AND WEB NEWS PORTALS - Kumar, Ankit; Thakur, Jyotsana; Mishra, Kaushik; Gupta, Rahul; Sharma, Abhishika (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This paper uses a comparative visual-design overview of credibility cues in Indian print newspapers and web-based news portals and how the use of layout, typography, color- schemes and imagery contribute to the overall perception of trust in the audience. Since news consumption is becoming less and less print-based and more and more digital-based, the visual grammar of credibility has started to develop in a manner that is both media-specifically constrained, and new design philosophically inclined. The research, based on mixed content-analytic and comparative research design, assesses various newspaper sources including The Hindu, The Times of India, and Dainik Bhaskar as well as digital portals, including NDTV, Scroll, and The Indian Express. It is the case those credibility cues are classified in terms of structural (layers of layout hierarchy, grid discipline), linguistic (headline typography, serif vs sans-serif orientation), and symbolic (color temperature, image framing, iconography) layers. It has been found that print newspapers are heavily dependent on visual traditions that are stable column structures, serif type dominance, and limited use of color to convey authority and editorial seriousness. Digital portals, in their turn, rely on vibrant layouts, more vivid colours, interactive types and multimedia additions to produce a sense of urgency and affordability. However, the contrasts do not hinder the incessant bargaining of the ratio between aesthetics, clarity and perceived reliability by both the media. The study will contribute to the ongoing discussions on the field of media design, digital journalism and visual communication given the fact that it offers a systematic way of approaching the process of visual encoding and decoding of credibility across media. It also indicates divergences created by mediums that affect trust to the reader and the need to have a design conscious editorial processes in the age of fast changing news systems.